The choice of adjuvant determines the cytokine profile of T cells in proteoglycan‐induced arthritis but does not influence disease severity. Issue 1 (13th December 2012) - Stoop, Jeroen N.; Tibbitt, Christopher A.; van, Willem; Robinson, John H.; Hilkens, Catharien M. U.
Abstract Rheumatoid arthritis (RA) is a debilitating autoimmune disease characterized by chronic inflammation of the synovial joints. Collagen‐induced arthritis (CIA) and proteoglycan‐induced arthritis (PGIA) are mouse models of inflammatory arthritis; CIA is a T helper type 17 (Th17) ‐dependent disease that is induced with antigen in complete Freund's adjuvant, whereas PGIA is Th1‐mediated and is induced using antigen in dimethyldioctadecyl‐ammonium bromide (DDA) as an adjuvant. To investigate whether the type of adjuvant determines the cytokine profile of the pathogenic T cells, we have compared the effect of CFA and DDA on T‐cell responses in a single arthritis model. No differences in incidence or disease severity between aggrecan‐T‐cell receptor transgenic mice immunized with aggrecan in either CFA or DDA were observed. Immunization with CFA resulted in a higher proportion of Th17 cells, whereas DDA induced more Th1 cells. However, the levels of interleukin‐17 (IL‐17) produced by T cells isolated from CFA‐immunized mice after antigen‐specific stimulation were not significantly different from those found in DDA‐immunized mice, indicating that the increased proportion of Th17 cells did not result in significantly higher ex vivo IL‐17 levels. Hence, the choice of adjuvant can affect the overall proportions of Th1 and Th17 cells, without necessarily affecting the level of cytokine production or disease incidence and severity.